The Necessary Correction to General Relativity of P. Y. Zhou and The Errors of Hawking, Einstein and Yang (Global Journal of Science Frontier Research, 2019)
Some claimed that after Einstein, Hawking could be the great physicist. However, his only verified prediction, the nonexistence of Higgs Boson, is proven wrong. His space-time singularity theorems have been proven as due to invalid physical assumptions, the unique sign for all coupling constants. Hawking also do not understand Einstein's unification and the existence of repulsive gravitation. Thus, the over-evaluation Hawking is due to out-dated knowledge in physics. In fact, both Hawking and Einstein had mistaken that E=mc2 were valid, and believed in Einstein's covariance principle. In 1983, the first correction to general relativity is given by Zhou Pei-Yuan of Peking University, who points out that Einstein's covariance principle is invalid. This is subsequently verified in 2010 by Lo with explicit examples. Moreover, Einstein's theoretical justification for his covariance principle is found surprisingly due to his invalid applications of special relativity. Zhou suggested that a valid physical gauge would be the harmonic gauge whose linearized approximation has been subsequently proven valid by the Maxwell-Newton Approximation. Thus, Zhou could be right. However, C. N. Yang claimed that Zhou was wrong due to Yang's misunderstanding of the gauge invariance.
Keywords: anti-gravity coupling; principle of causality; repulsive gravitation; E = mc2